PEMANFAATAN BIOCHAR DAN KOMPOS BLACK SOLDIER FLY PADA FITOREMEDIASI TANAH TERCEMAR TIMBAL DAN PENGARUHNYA TERHADAP PERTUMBUHAN SERTA HASIL TANAMAN SAWI (Brassica juncea L.) - Fathia Meidy Nurindriana; Kurniawan Sigit Wicaksono (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2022)
Unhealthy agricultural activities possibly caused damage due to pollution from dangerous substances that accumulate as residues. Pesticides can be one of the factors causing soil pollution; one of the reasons is the presence of lead (Pb). This study aimed to elucidate the potential use of sunflower (Hellianthus annus Linn) for phytoremediation Pb contaminated soil. Phytoremediation optimization was upported by the addition of ameliorants in the form of BSF (black soldier fly) compost and biochar. The research was carried out in two stages; the first stage was the utilization of sunflower for phytoremediation of Pb contaminated soil. The second stage was the use of post-phytoremediation soil for planting mustard plants. The results showed that phytoremediation efficiency ranged from 45.74-67.17%, indicating that the sunflower plant was quite effective as Pb accumulator plant. The application of biochar and BSF compost was able to show a higher value than the control treatment to maximize the phytoremediation process. Mustard plants grown on soil that has been remediated showed better growth and biomass yields than that grown on soil that had not been subjected to phytoremediation.